Estudo do genótipo cagA da Helicobacter pylori e sua associação com os fatores socioeconômicos e as afecções gástricas no Oeste do Maranhão, Brasil - LIMA, Victor Pereira (2021)
Approximately more than half of the world's population is infected with Helicobacter pylori. However, the prevalence of the infection varies between different regions, with higher rates in developing countries compared to developed ones. The mechanisms involved in the development of gastric diseases related to H. pylori infection depend on host genetics, environmental factors and bacterial virulence. Among the virulence factors, the cagA genotype stands out, being directly associated with the most severe gastric affections, due to the encoding of the CagA oncoprotein injected into the gastric epithelial cell through the type IV secretion system, which alters the transduction signals, mechanisms of apoptosis and the cytoskeleton of cells. Furthermore, other host factors can influence the pathogenesis of H. pylori infection, such as socioeconomic conditions and risk behaviors. Thus, the aim of this study was to identify cagA-positive strains of Helicobacter pylori in Maranhão, investigating associations between genotype, socioeconomic data and gastric disorders. Study conducted from October 2015 to February 2018, in a public endoscopy service, in Imperatriz, Maranhão. Information on socioeconomic factors was collected through a semi- structured form applied in the waiting room of the service. Clinical characteristics and endoscopic diagnoses were obtained from the patients' charts. The genotyping of the strains was performed by polymerase chain reaction (PCR) in gastric tissue samples, with a positive urease test for H. pylori. To verify the association between variables, Pearson's chi-square test was applied (significance level of p<0.05) and its effect was measured using the odds ratio. The study was approved by the Ethics Committee for Research with Human Beings of the Federal University of Maranhão. The study included 751 dyspeptic patients with a mean age of 43.8 years, 68.3% were women, 50.3% had less than 10 years of education, 66.7% married, 73.8% had income monthly less than the minimum wage, 83.5% lived with less than five people, 55.7% did not have a sewage system, 52.5% consumed untreated water, 67.5% did not drink and 82% did not smoke. The prevalence of H. pylori was 52.7%, with an association with income below the minimum wage (p < 0.0001; OR: 1.94; 95% CI: 1.39–2.70) and consumption of untreated water (p=0.03; OR: 1.37; 95% CI: 1.02–1.83). Men (p=0.01; OR=0.27; 95%CI=0.094-0.817) were less likely to develop gastritis. The prevalence of the cagA genotype was 25.5% of the strains. Low income was inversely associated with the presence of the cagA gene, even after adjustments. Untreated water was associated with the presence of the cagA genotype in univariate (OR = 2.55; 95% CI: 1.008-6.48; p = 0.03) and multivariate (OR = 2.89; 95% CI: 1.08-7.67; p = 0.03). There was no association between the cagA-positive strains with gastritis, peptic ulcer and esophagitis affections. The study showed that untreated water was associated with the presence of the Helicobacter pylori cagA genotype in southwestern Maranhão and was not associated with the investigated gastrointestinal diseases.